Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0198855
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized aerobic exercise trial in older HIV-infected men: Insights into strategies for successful aging with HIV

Abstract: BackgroundHIV-infected adults have increased risk for age-related diseases and low cardiorespiratory fitness that can be prevented and improved with exercise. Yet, exercise strategies have not been well studied in older adults with HIV and may require substantial adaptation to this special population.ObjectiveTo determine the safety and efficacy of aerobic exercise in older HIV-infected men in a randomized trial comparing different levels of exercise intensity.MethodsWe conducted a pilot exercise trial in 22 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…The CBE intervention involved a combination of aerobic, resistance, balance and flexibility training, and was not specifically tailored to enhancing aerobic capacity. Oursler and colleagues found a significantly greater increase in V O 2 max of 3.6 ml/kg/min among people living with HIV who completed 16 weeks of vigorous intensity aerobic exercise compared with no change in V O 2 max among participants who completed 45 minutes of moderate-paced walking [10]. Erlandson and colleagues [62] conducted a thrice weekly 24-week aerobic and resistance exercise intervention comparing older adults living with HIV and without HIV (50-75 years) where after 12 weeks of moderate-intensity of exercise individuals were randomized to 12 additional weeks of moderate or high intensity exercise.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…The CBE intervention involved a combination of aerobic, resistance, balance and flexibility training, and was not specifically tailored to enhancing aerobic capacity. Oursler and colleagues found a significantly greater increase in V O 2 max of 3.6 ml/kg/min among people living with HIV who completed 16 weeks of vigorous intensity aerobic exercise compared with no change in V O 2 max among participants who completed 45 minutes of moderate-paced walking [10]. Erlandson and colleagues [62] conducted a thrice weekly 24-week aerobic and resistance exercise intervention comparing older adults living with HIV and without HIV (50-75 years) where after 12 weeks of moderate-intensity of exercise individuals were randomized to 12 additional weeks of moderate or high intensity exercise.…”
Section: Plos Onementioning
confidence: 97%
“…Exercise can reduce the risk of multimorbidity and improve health outcomes for adults living with HIV [9][10][11]. Systematic review evidence demonstrated that engaging in aerobic, resistive or combined aerobic and resistive exercise at least three times per week can improve cardiorespiratory fitness, strength and quality of life outcomes among adults living with HIV [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The 6-min walk test (6MWT) has been used to measure functional exercise capacity in a number of studies. Casanova et al ( 2011 ) conducted a cross-sectional, international, multicentre study with normal volunteers aged 40–49 years and found that the average man walked 650 m and the average woman walked 600 m. In one older sample of PWH (Oursler et al 2018 ), the average baseline distance walked during the 6MWT was 551 m (standard deviation [SD] = 33 m). In a different HIV-infected sample with an average age of 52 years, men walked an average distance of 415 m whilst women walked an average distance of 367 m (Oliveira et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among women living with HIV, engaging in vigorous physical activity was associated with improved cardiorespiratory function. Oursler et al (2018) suggested, after the use of a randomized control trial, that moderate-to-high intensity aerobic exercise has the capacity to increase endurance and ambulatory function in older HIV-infected men. However, increased cardiorespiratory fitness was only observed with high intensity aerobic exercise.…”
Section: Exercise and Physical Health And Functionmentioning
confidence: 99%